1998
DOI: 10.1046/j.1471-4159.1998.70041593.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification, and Encephalitogenicity of Recombinant Human Myelin Oligodendrocyte Glycoprotein

Abstract: Myelin oligodendrocyte glycoprotein (MaG), a putative autoantigen in multiple sclerosis (MS), is a quantitatively minor component of the CNS. In view of the difficulties associated with the purification of MOG from brain tissues, the extracellular domain of human MOG corresponding to the N-terminal 121 amino acids was expressed in Escherichia co/i as a glutathione sulfotransferase fusion protein. The expressed protein was localized to inclusion bodies, and varying the growth parameters resulted in the solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Previous analyses suggested that the CNS infiltrate in mice immunized with human MOG protein was predominantly mononuclear (3,21), but it is difficult to determine from the published data whether PMN were present in these lesions. In the experiments presented in this study with mice immunized with human MOG protein, it is likely that PMN were attracted to the CNS by as yet unidentified chemotactic factors.…”
Section: Discussionmentioning
confidence: 95%
“…Previous analyses suggested that the CNS infiltrate in mice immunized with human MOG protein was predominantly mononuclear (3,21), but it is difficult to determine from the published data whether PMN were present in these lesions. In the experiments presented in this study with mice immunized with human MOG protein, it is likely that PMN were attracted to the CNS by as yet unidentified chemotactic factors.…”
Section: Discussionmentioning
confidence: 95%
“…Human MBP was purified from white matter of human brain, as described (Deibler et al, 1972). Endotoxin-free extracellular domain (rMOG) was prepared as described previously (Bettadapura et al, 1998) (184)(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199) were synthesized and HPLC purified (Ͼ 95% purity) by Severn Biotech Ltd (Worcester, UK). The amino acid sequences of the peptides are shown in Table II.…”
Section: Cell Culture Media and Antigensmentioning
confidence: 99%
“…It is also important to note that all expression systems that we have identified produce fusion proteins consisting of the MOG extracellular domain, various purification tags, and often additional sequences that we cannot identify. Most incorporate either human or rat MOG 1-125 (Bettadapura et al, 1998), and therefore when used in mice represent a cross-reactive response not ideal for some investigations of autoimmune-specific cell interactions.…”
Section: Introductionmentioning
confidence: 99%